Labour Productivity Measurement Method for Malaysian Housing Industry - Lee, Wah Peng (2005)
The industrialised building system (IBS) was introduced in Malaysia in 1966, but it failed to establish itself though there is a sustained large market for residential projects. One of the main reasons behind this failure is a lack of scientific data on labour productivity in the construction industry. Hence, the objective of this study is to establish a labour productivity measurement method for the Malaysian housing construction industry. Labour productivity (manhours/m2) is defined as the manhours (the multiplication of number of workers and work time) required to complete a structural element of a house. Two data collection methods were used to collect the labour productivity data, namely time study on-site observation (ideal labour productivity) and survey questionnaire (actual and pre-planned labour productivity). For the time study on-site observation method, a total of 499 ideal labour productivity data were obtained from seven residential projects constructed between January 2003 and April 2004. Results indicated that the mean ideal labour productivity for conventional building system was 4.20 manhours/m2 followed by cast in-situ table form 2.70 manhours/m2), cast in-situ tunnel form (1.88 manhours/m2) and precast concrete system (1.33 manhours/m2). The mean cycle time measured in days for conventional building system, cast in-situ table form system, cast in-situ tunnel form and precast concrete systems were 4.93, 3.91, 2.90 and 2.3 1 days respectively. The mean crew size for conventional building system was 24 workers while for IBS was 22 workers. The subsequent analysis developed the ideal labour productivity measurement method using multiple regression analysis. The results indicated that the independent variables, namely type of building system, crew size, gross building floor area and floor level have significant impact on ideal labour productivity with coefficient of determination, R~ of 82.1%. A total of 102 respondents which included 72 contractors, 19 consultants and 1 1 developers responded to the survey questionnaire. The data obtained from the questionnaire were actual labour productivity data from actual residential projects and pre-planned labour productivity from hypothetical projects. The results indicated that the mean actual labour productivity for conventional building system was 7.00 manhours/m2 compared to IBS of 2.10 manhours/m2 while the mean pre-planned labour productivity for conventional building system was 7.40 manhours/m2 compared to IBS of 2.13 manhours/m2. Finally, the factors causing the gaps between actual and ideal labour productivity were established and ranked.